The Effect of Palm Fiber as a Material of Added Fiber and Charcoal Powder as Cement Subtitution Against Strong Concrete Press - Acep Hidayat; Unggul Pratama (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Palm fibers are natural fibers that are difficult to rot because there is no decomposer that can decompose the fibers. In addition, in Indonesia there are a lot of palm plants where the fibers are taken from the tree. The charcoal briquette powder is the fine grains of briquette charcoal that is mashed and contains silica. This study aims to determine the effect of using palm fiber as an added material for fiber and charcoal briquette powder as a substitute for cement in the concrete mixture on the compressive strength of concrete. This study uses a mixture of palm fiber as much as 0.75 %, 1.50 %, 1.75 % and 2.75 % from the weight of fine aggregate, as well as charcoal briquettes powder 5 %, 5 %, 10 %, and 15 % of the weight of cement. The compressive strength test was carried out on the 7th, 14th, 21st, and 28th days. The highest compressive strength value was obtained in variation V.2 with a mixture of 2.75% palm fiber + 5% briquette charcoal powder on the 21st day of testing of 20.02 Mpa